Relationship between educational background and patient motivation to seek dental treatment - Kusumawardani, Anisa; Zahari, Alia Farina; Nik Yusof, Nik Nurfathin; Tin, Myo Han; Hasan, Taufiq Hidayat; Abllah, Zurainie (2014)
Background: There is high prevalence of dental diseases shown in epidemiological studies, yet, not more than half adults visiting the dentist within a year. Majority of people seek dental treatment are mainly to reduce pain.1 Several factors that affect patients’ oral health seeking behavior includes education, gender, socio-economic status, rural characters, dental health insurance and the need for dental treatment.2 The barriers in regular dental care include dental anxiety, price, income, the distance of travel to get care and preference to preserve teeth.1 Objective: To determine the relationship between educational background and patient motivation to seek dental treatment. Material and methods: A cross-sectional study was conducted among 120 patients of 18-year-old and above who attended IIUM Dental Polyclinic by using simple random sampling method. A set of questionnaire consists of 13 questions with Likert scale3, was distributed to patients during clinical hours to assess their motivational level to seek dental treatment. The motivation levels were categorized into low (score below 26), moderate (score 27-51), and high motivation (score 52-65). An X2 and ANOVA test were applied to test the relationship between educational background and motivation level of the patients. Results: In the study, out of 120 patients, 89 patients (74.2%) showed moderate level of motivation, 31 patients (25.8%) showed high level of motivation and none (0%) showed low level of motivation. From high motivation level group, patients with certificate/diploma showed the highest percentage (38.7%), followed by first degree/higher degree (32.3%), SPM/STPM (29.0%) and below SPM (0%). While from moderate motivation level group, patients with certificate/diploma also showed the highest percentage (29.2%), followed by first degree/higher degree (25.8%), SPM/STPM (23.6%) and below SPM (21.3%). There was a significant association (p=0.048) between educational background and patient motivation to seek dental treatment. Conclusion: There was a significant relationship between educational background and patient motivation to seek dental treatment in IIUM dental polyclinic. Recommendation: Oral health education and promotion should be focused on people with low education background.